(untitled) (International Journal of Architecture and Urbanism, 2021)
Taman Merah is one of the thematic parks planned by the residents of Kampung Pelangi to provide a forum for activities and meet the needs of green open space for the environment by utilizing the empty land in Kampung Pelangi environment. This activity is a service program communities that aims to help residents plan and design the Red Park according to their needs. The method that used is the landscape architecture design method with a sustainable landscape approach, starting from site surveys, identifying people’s needs and activities, studying literature related to sustainable landscape criteria to be applied to the Taman Merah design concept, compiling programming and design concepts. The results of the study obtained are the criteria for sustainable landscapes that are applied in the design concept including environmental, economic, socio-cultural, aesthetic, and institutional aspects. The five criteria were identified to be used as the basis for the Taman Merah design concept. The sustainability of these five aspects aims to improve the quality of the environment, improve the residents’ economy, a forum for the actualization of socio-cultural activities, provide interesting place experiences, and foster collaboration between residents and community groups in Kampung Pelangi RW 9 Joyogrand Housing, Merjosari Village, Malang City.